GCMeval – An interactive tool for evaluation and selection of climate model ensembles - Kajsa M. Parding; Andreas Dobler; Carol F. McSweeney; Oskar A. Landgren; Rasmus Benestad; Helene B. Erlandsen; Abdelkader Mezghani; Hilppa Gregow; Olle Räty; Elisabeth Viktor; Juliane El Zohbi; Ole B. Christensen; et al. (Climate Services, 2020)
We present an interactive tool for selection and evaluation of global climate models. The tool is implemented as a web application using the ”Shiny” R-package and is available at https://gcmeval.met.no. Through this tool, climate models of the CMIP5 and CMIP6 ensembles can be ranked and compared based on their representation of the present climate, with user-determined weights indicating the importance of different regions, seasons, climate variables, and skill scores. The ranking can be used to eliminate the climate models with poorest representation of the present climate. As further guidance, the projected regional mean temperature and precipitation changes for all climate models are displayed in a scatterplot for a chosen season, emission scenario, and time horizon. Ranks and projected changes for a subset of climate models are compared to the whole ensemble. Subsets can be selected interactively and the tool provides on-the-fly visualizations. The combined information of the projected climate change and model ranking can be used as an aid to select subsets of climate models that adequately represent both the present day climate and the range of possible future outcomes. Allowing weighting of different metrics introduces a subjective element in the evaluation process and demonstrates how this can affect the ranking. The tool also illustrates how the range of projected future climate change is sensitive to the choice of models.